The False Promise of "Neoliberal Cinderella": Deconstructing Gender and Social Class Discourse in Anora (2024) - Rahman, Fadhlur (Saree: Research in Gender Studies, 2025)
ABSTRACT ENGLISHFilm is a discursive sphere where cultural meanings are constructed and debated through visual storytelling. Therefore, it is significant to expose binary contradictions in neoliberal gender ideology and reveal structural violence against women hidden behind narratives of social mobility in film. This study, thus, aims to unravel the complexity of gender and class representations in Anora (2024) through a critical analysis of “Neoliberal Cinderella” discourse, which frames labour relations as romance and shifts the costs of social reproduction onto women's bodies. This research employs interpretive qualitative study with two mutually reinforcing analytical frameworks. First, Derrida's Deconstruction to identify and dismantle dominant binary oppositions (love versus money, spontaneity versus strategy, reality versus fantasy) through an in-depth reading of mise-en-scène, dialogue and material markers. Second, Marxist-feminist perspective is utilised to map the political economy of affective labor, the mechanisms of commodification through gifts and access, and the unequal distribution of risks and costs affecting the main character, Ani. The results show that Anora both produces and disrupts the neoliberal Cinderella myth by revealing the hidden costs behind the promise of social mobility (social climbing): fragmented time, exploited emotions, and commodified security. The movie reveals that social mobility is a lease, not a right, and that love is used to glorify labour contracts. This paper proposes a methodological bridge of Marxist-feminist and deconstruction for cultural criticism that demands structural redistribution and recognition of affective labour as real work that is entitled to protection, compensation, and dignity. ABSTRACT INDONESIANFilm merupakan ruang diskursif di mana makna-makna budaya dibangun dan diperdebatkan melalui bahasa sinematik, sehingga mampu mengungkap kontradiksi dalam ideologi gender neoliberal dan mengungkap kekerasan struktural terhadap perempuan yang tersembunyi di balik narasi mobilitas sosial. Studi ini bertujuan untuk mengurai kompleksitas wacana gender dan kelas dalam film Anora (2024) melalui analisis narasi “Neoliberal Cinderella” yang menggambarkan hubungan kerja sebagai romansa dan mengalihkan beban reproduksi sosial dalam tubuh perempuan. Metode penelitian menggunakan studi kualitatif interpretatif dengan dua alat analitis yang saling memperkuat. Dekonstruksi Derrida digunakan untuk mengidentifikasi dan membongkar oposisi biner yang dominan seperti cinta versus uang, spontanitas versus strategi, realita versus fantasi, melalui analisis mendalam mise-en-scène, dialog, dan tanda-tanda material di dalam film. Kemudian teori feminis-Marxis digunakan untuk memetakan ekonomi politik kerja afektif, mekanisme komodifikasi melalui hadiah dan akses kekuasaan, serta distribusi risiko dan “harga” yang harus ditanggung dan “dibayar” oleh karakter perempuan dalam fiim ini. Hasil dari analisis menunjukkan bahwa Anora membongkar fantasi Cinderella modern dimana mobilitas social yang dijanjikan hanya akan selalu mengorbankan stabilitas hidup, mengeksploitasi emosi dan menjadikan rasa aman sebagai komodifikasi. Film ini mengungkapkan bahwa mobilitas sosial adalah bersifat sementara, bukan hak yang berkelanjutan, dan cinta hanya digunakan untuk menghormati kontrak kerja. Penelitian ini menawarkan kerangka-metodologi teori baru (dekonstruksi-feminis-Marxis) untuk kritik budaya yang menuntut redistribusi struktural dan pengakuan terhadap pekerja emosional sebagai pekerjaan nyata yang berhak atas perlindungan, kompensasi, dan martabat.